IMPLEMENTATION OF SUSTAINABLE STRATEGIES IN SPORTS EVENT MANAGEMENT: ANALYSIS OF SUCCESS FACTORS AND KEY BARRIERS - Surbatovic, Jovan; Milić, Marko Kimi (Sport - nauka i praksa, 2026)
This paper analyzes the implementation of sustainable (“green”) strategies in sports event management. The objective of the study was to identify the key barriers to successful implementation of these strategies and to formulate recommendations for improving practice. A combination of qualitative and quantitative methods was used, including structured questionnaires, semi-structured interviews, document analysis, and direct observation. Three sporting events of varying scales held in Serbia in 2023 were analyzed. The implementation of sustainable strategies was found to depend on the size of the event and the available resources. The main obstacles to implementing these strategies were high costs, lack of skilled personnel, and logistical barriers. A positive impact of involving the local community and using digital technologies on the effectiveness of ecological measures was confirmed. The results clearly indicate that organizational capacity and resources are key factors for the successful application of sustainability. The identified barriers suggest the need for a systematic approach, greater institutional support, and continuous staff education. Integrating sustainability into the organization of sporting events requires detailed planning, institutional backing, and education. The recommendations presented in this paper can help organizers to more effectively implement sustainable practices and overcome existing barriers.
Keywords: sustainability; green strategies; sporting events; management; ecological practices